2013
DOI: 10.1159/000347002
|View full text |Cite
|
Sign up to set email alerts
|

G-Protein-Coupled Receptor Kinase-5 Mediates Inflammation but Does Not Regulate Cellular Infiltration or Bacterial Load in a Polymicrobial Sepsis Model in Mice

Abstract: NFκB-dependent signaling is an important modulator of inflammation in several diseases including sepsis. G-protein-coupled receptor kinase-5 (GRK5) is an evolutionarily conserved regulator of the NFκB pathway. We hypothesized that GRK5 via NFκB regulation plays an important role in the pathogenesis of sepsis. To test this we utilized a clinically relevant polymicrobial sepsis model in mice that were deficient in GRK5. We subjected wild-type (WT) and GRK5 knockout (KO) mice to cecal ligation and puncture (CLP)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
41
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 44 publications
(67 reference statements)
1
41
3
Order By: Relevance
“…To determine the relative levels of a specific RNA transcript, RNA was isolated from snap-frozen tissue using the Qiagen RNeasy minikit according to the manufacturer's protocol and as described earlier (40). Reverse transcription (RT) was carried out with 1 g of RNA using the Promega cDNA synthesis kit.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the relative levels of a specific RNA transcript, RNA was isolated from snap-frozen tissue using the Qiagen RNeasy minikit according to the manufacturer's protocol and as described earlier (40). Reverse transcription (RT) was carried out with 1 g of RNA using the Promega cDNA synthesis kit.…”
mentioning
confidence: 99%
“…Reverse transcription (RT) was carried out with 1 g of RNA using the Promega cDNA synthesis kit. Quantitative RT-PCR (qRT-PCR) was performed with ABI Fast 7500 (Applied Biosystems), and all genes were normalized to hypoxanthine phosphoribosyltransferase (HPRT) as previously described (40). The following primers were used for the respective genes: tumor necrosis factor alpha (TNF-␣) forward, TCT CATCAGTTCTATGGCCC-3; TNF-␣ reverse, GGGAGTAGACAAGCT ACAAC; IB␣ forward, TGG CCA GTG TAG CAG TCT TG; IB␣ reverse, GAC ACG TGT GGC CAT TGT AG; interleukin 6 (IL-6) forward, ACA AGT CGG AGG CTT AAT TAC ACA T; IL-6 reverse, TTG CCA TTG CAC AAC TCT TTT C; keratinocyte chemoattractant (KC) forward, CTTGAAGGTGTTGCCCTGAG; KC reverse, TGGGGACACCTTTTAG CATC; macrophage inflammatory protein 2 (MIP2) forward, GGCAAG GCTAACTGACCTGGAAAGG; MIP2 reverse, ACAGCGAGGCACATG AGGTACGA; HPRT forward, AAG CCT AAG ATG AGC GCA AG; HPRT reverse, TTA CTA GGC AGA TGG CCA CA.…”
mentioning
confidence: 99%
“…Furthermore, GRK5 levels have been shown to be modulated in different disease conditions, including neurodegenerative disorders (14), cancers (15), sepsis (16), and cardiac failure (17,18). In recent studies, we showed that GRK5 is an important regulator of endotoxemia and polymicrobial sepsis pathogenesis (19,20). Although GRK5 is highly expressed in normal (9,21) and diseased (22) airways, its role in lung infection is unknown.…”
mentioning
confidence: 99%
“…To determine changes in the number of cells, cells were counted using a hemocytometer. For flow cytometry, cells were also labeled with cell surface markers for various immune cells (Gr-1, CD11b, F4/80, CD11c, B220, CD3, and Ly6C), and data were acquired using an LSR II flow cytometer (BD Biosciences) and were analyzed using FlowJo software (Tree Star, Inc., Ashland, OR, USA) as described previously (19).…”
mentioning
confidence: 99%
See 1 more Smart Citation